Steel Structures Research: Design for Deconstruction with Demountable Composite Beams and Floor Systems - Liu, Judy (Engineering Journal, 2016)
Ongoing and recently completed research on deconstructable steel-concrete composite beams and floor systems forsteel frame buildings is presented. This research includes demountable beam-slab connectors, deconstructable compositefloor systems with precast concrete planks, and lightweight modular two-way steel flooring systems.